1985
DOI: 10.1161/01.res.56.3.310
|View full text |Cite
|
Sign up to set email alerts
|

Coronary pressure-flow relationships. Controversial issues and probable implications.

Abstract: On the basis of the material discussed, our current assessments of the controversial points mentioned at the beginning of this article may be summarized as follows: Pf = 0, the minimum back pressure to coronary flow associated with a measurable conductance, is indeed greater than coronary outflow pressure (and usually left ventricular diastolic pressure, as well). Pf = 0 needs to be taken into account in attempts to determine coronary driving pressure. In maximally vasodilated beds, Pf = 0 derived from diastol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
50
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(55 citation statements)
references
References 60 publications
(75 reference statements)
5
50
0
Order By: Relevance
“…This phenomenon has been and independent agonists in the same animals before and demonstrated to occur in the coronary circulation during after the development of CHF. The data demonstrate that both systole and diastole [7,8,16] so that coronary back the increased LV diastolic pressure in the failing heart is pressure exceeds venous pressure measured in the coronary associated with an increased P that contributes to the sinus or right atrium [17]. The effective back pressure to zf decreased response to the vasodilators.…”
Section: 2mentioning
confidence: 84%
“…This phenomenon has been and independent agonists in the same animals before and demonstrated to occur in the coronary circulation during after the development of CHF. The data demonstrate that both systole and diastole [7,8,16] so that coronary back the increased LV diastolic pressure in the failing heart is pressure exceeds venous pressure measured in the coronary associated with an increased P that contributes to the sinus or right atrium [17]. The effective back pressure to zf decreased response to the vasodilators.…”
Section: 2mentioning
confidence: 84%
“…20 In contrast, Klocke and his colleagues pointed out that the rate of pressure change is very slow and thus incapable of causing large capacitive effects at the end of a long diastole. 21 In fact, their recent study indicated a relatively high Pzf in some steady-state pressure flow curves in which extremely low flows were attained. 22 It is still controversial as to whether Pzf exist or not.…”
Section: Discussionmentioning
confidence: 96%
“…12 Mean coronary pressure at the cannula side arm -the pressure at which forward coronary flow ceased (Pzf), was used for coronary perfusion pressure in calculating coronary vascular resistance during antegrade perfusion of the LCX after cannulation. 20 …”
Section: +mentioning
confidence: 99%
“…After cannulation of the LCX, coronary resistance to antegrade reflow was calculated using the difference in mean coronary pressure and pressure zero flow (Pzf) for that artery as an approximation of coronary perfusion pressure. 20 Back pressure on a coronary artery when forward flow ceases (Pzf) has been shown to be approximately 15 mm Hg for the LAD coronary artery in pigs. 15 - 21 Pzf in our control pigs averaged 18 mm Hg for the LCX coronary artery.…”
mentioning
confidence: 99%